86.1k views
5 votes
For the following system, tell which equation you would first use to solve for a variable in the first step of the substitution method. Explain your choice.

-2x + y = -1
4x + 2y = 12

User Luqmaan
by
5.0k points

1 Answer

7 votes

Answer:

start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2

Explanation:

-2x + y = -1 is most easily solvable for y: y = -1 + 2x.

Note that we can reduce the second equation to 2x + y = 6

Substituting this -1 + 2x for y in this new version of the second equation yields:

2x + (-1 + 2x) = 6

Simplifiying, we get:

2x - 1 + 2x = 6, or 4x = 7. Then x = 7/4.

Again: start the solution either by solving the first given equati9on for y or by reducing the second equation by dividing all three terms by 2.

User Maccath
by
6.2k points